Royale Absence - Henri Justin (Sillages Critiques)
The article is a chip off a projected study of Poe’s rewritings of Shakespearian tragedy. The moving force at the centre of “The Purloined Letter” is the spectral presence of the King, but a close reading of “The Purloined Letter” and “William Wilson” as rewritings of Hamlet reveals how much the play by Shakespeare partakes of the structure of the doppelgänger tale. As the play develops, the royal spectre loses force, till it appears obvious that only an empty mirror separates Hamlet from Claudius. Finally, the last page of “The Purloined Letter” goes as far as to suggest that the mirror tucked away within literary texts is the sovereign source of the poetry in them – a royal absence.